Pelatihan Dan Pendampingan Rebranding Logo Sebagai Upaya Peningkatan Daya Saing Usaha Kepada Para Pelaku UMKM Di Kelurahan Gebang Putih (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Logo rebranding training and mentoring as an effort to increase business competitiveness for MSMEs in Gebang Putih sub-district. Gebang Putih village is one of the villages in the Sukolilo sub-district. Gebang Putih sub-district has quite a number of MSMEs, some of which are quite large, but not a few are still pioneering. we identified one of the problems lies in the lack of branding on the products being marketed, one of which is the problem of rebranding the MSMEs logo. Some MSMEs in the Gebang Putih sub-district still have a logo design that tends to be simple and there are even a number of MSMEs in the Gebang Putih sub-district that do not yet have a logo. Branding is something that is in a product or service such as a name, sign, symbol, logo, or a combination of all that aims to identify a product or service. the purpose of branding is to introduce a product or to the wider community, build public trust in a product, and to shape public perception of a product being sold. Based on the above problems, a logo rebranding training and mentoring program was implemented for MSMEs in the Gebang Putih sub-district. The training and assistance is intended so that MSMEs can recognize the importance of branding and make their own logo designs more attractive.